Brain Drain in Higher Education. The Impact of Job Stress and Workload on Turnover Intention and the Mediating Role of Job Satisfaction at Universities - Anees, Rao Tahir; Heidler, Petra; Cavaliere, Luigi Pio Leonardo; Nordiana, Ahmad Nordin (European Open Science Publishing, 2021)
This study seeks to determine the impact of job stress and workload on turnover intention along with the mediation role of job satisfaction. A total of 140 academics and management personnel participated in this study’s survey. A partial least square structural equation modeling was used for data analysis. The results show that job stress and workload have a positive effect on turnover intention, while job satisfaction mediates the relationship between job stress, workload, and turnover intention. Future research could adapt and adopt the herein used methodology and research topic to other countries or in other industries.